Steadying the ladder: China's agricultural and rural development engagement in Africa - Chen, Kevin Z.; Hsu, Claire; Fan, Shenggen (Emerald Publishing Limited, 2014)
This paper aims to draw lessons from China's development experiences, particularly in the areas of agricultural and rural development, to increase growth and reduce poverty in Africa South of the Sahara. It also examines China's rising economic involvement in Africa and makes recommendations for how the win-win outcomes from this engagement can be strengthened.– In this paper, the authors compare the trends in economic and agricultural growth, as well as poverty and hunger reduction, in China and Africa South of the Sahara. The authors then examine strategies for development – in particular agricultural and rural development – and poverty reduction. Next, the authors review China's economic engagement in Africa in the areas of trade, investment, aid, and technical cooperation.– Having conducted a comparative review of China and Africa's distinct development paths and current policy contexts, the authors discuss China's development lessons for Africa South of the Sahara and policy recommendations for China-Africa engagement related to agricultural and rural development, openness and liberalization, evidence-based policymaking, pro-poor policies, institutions and capacity, rising inequality, and environmental degradation.– This paper rigorously integrates China's positive and negative development lessons for Africa in light of the most recent research on emerging domestic and international development strategies.